Report of the Committee for Training in Evaluation - Planning Commission (Planning Commission, 1979)
In pursuance of the recommendations of the Conference of the Heads of State Evaluation Organisations held in New Delhi in November, 1977, the Government of India vide their O.M. No. PEO/10-6/77-TE, dated June 23, 1978 set up a Committee for Training in Evaluation under the chairmanship of Secretary, Planning Commission (Appendix I). Although the Committee was initially constituted for a period of six months, its tenure had to be extended until September 30, 1979 in view of the organisation of three experimental Regional Workshops for the Senior1 level evaluation personnel and preparing the syllabus for the Supervisory2 level personnel by a sub-committee. On his taking over as Secretary, Planning Commission from Dr. Ajit Mozoomdar, Shri S. S. Puri assumed the chairmanship of the Committee w.e.f. August 1, 1979. The Committee consisted of 20 members, but 3 of them showed their inability to work on it in view of their pre — occupation. An additional member, Dr. J. N. Mongia, was co-opted by the Chairman on September 13, 1978. The final composition of the Committee was as follows
Programme Evaluation Organisation Planning Commission Government of India New Delhi